A randomized sequential allocation study on the optimum programmed intermittent epidural boluses interval time with different concentrations of ropivacaine combined with the dural puncture epidural technique for labor analgesia - Mao, Jingjing; Chen, Yi; Sun, Linsen; Xu, Xiaoxiao; Xu, Kai; Ren, Tingting; Xiong, Xiangsheng; Zhao, Weibing (Frontiers in Pharmacology, 2025)
BackgroundThe combined technique of programmed intermittent epidural boluses (PIEB) and dural puncture epidural (DPE) is currently considered a more effective mode for labor analgesia. We investigated the optimal interval time for PIEB administration with different concentrations of ropivacaine combined with the DPE for labor analgesia.MethodsNinety patients with cervical dilation of <5 cm and a VAS score >5 were randomly assigned to receive labor analgesia with ropivacaine at concentrations of 0.075% (0.075% group), 0.1% (0.1% group), and 0.125% (0.125% group). In each group, an initial administration of a combination of ropivacaine 12 mL and sufentanil 0.3 μg/mL was followed by an additional dose of ropivacaine 10 mL and sufentanil 0.3 μg/mL after 30 min. The initial PIEB interval time was set at 40 min for the first patient in each group, and subsequent interval times for the following patients were adjusted based on meeting analgesic needs (VAS score ≤1) with a gradient of 10 min. The primary outcome was the ED90 of interval time required to achieve analgesic needs during PIEB with different concentrations of ropivacaine, employing an up-and-down sequential allocation method.ResultsThe optimal PIEB interval times for ropivacaine concentrations of 0.075%, 0.1%, and 0.125% were determined to be 40.9 (95% CI, 35.3–45.8), 45.3 (95% CI, 39.3–51.5), and 52.9 (95% CI, 46.8–59.3) minutes respectively, while comparable maternal and neonatal outcomes were observed across all groups.ConclusionWhen PIEB is combined with DPE for labor analgesia, the optimal PIEB interval times for ropivacaine concentrations of 0.075%, 0.1%, and 0.125% were determined to be 41, 45, and 53 min respectively.